Mechanical Determinants of the U-Shaped Speed-Energy Cost of Running Relationship - Carrard, Apolline; Fontana, Elisa; Malatesta, Davide (Frontiers in Physiology, 2018)
Purpose. The aim of this study was to investigate the relationship between the energy cost of running (Cr) and speed and its mechanical determinants by comparing running in normal [100% body weight (BW)] and reduced (20% and 60% BW) gravity conditions at several speeds (2.25, 3.17, 4.08 and 5.00 m∙s-1) with experienced runners. Methods. Twelve experienced runners (24.6±5.4 yr) ran on an AlterG treadmill in a partially randomized order at the four running speeds and at the three gravity conditions in order to assess Cr, spatiotemporal parameters, spring-mass characteristics and elastic energy (EL) during running. Results. For the three gravity conditions, the speed-Cr per kg of body mass relationship was curvilinear (significant speed effect: P<0.001) and was significantly downward shifted with gravity (100%>60%>20% BW; P<0.001). EL, expressed in J∙step-1, was significantly higher at 100% BW than at 60% and 20% BW and at 60% BW than at 20% BW (significant gravity effect: P < 0.001) with a significant increase in EL per step depending on speed for the 3 gravity conditions (P < 0.001). EL, expressed in J∙kg-1∙m-1, was significantly downward shifted with gravity (100%>60%>20% BW; P<0.001), with no significant speed effect (P = 0.39). Conclusions. Our findings showed that, for the three gravity conditions, the speed-Cr relationship was curvilinear, and the optimization of the stretch-shortening cycle and muscle activation in the muscle-tendon unit may be involved to explain these U-shaped relationships, especially at normal terrestrial gravitational conditions (100% BW). The U-shaped speed-Cr per kg of the body mass relationship was shifted downward in hypogravity conditions, which was characterized by decreased EL compared to 100% BW. These mechanical mechanisms may contribute to the disproportional decrease in Cr per kg of body mass relative to gravity.